Relating Genesis 16 to sexual abuse in the church: Hagar as a biblical parallel - Lucas, Philippa (Anglican theological review, 2023)
Sexual abuse within the church is not a new phenomenon, with revelations about abuse within the catholic church having long been on the public radar. However, in the wake of the #Metoo movement, recent years have seen an increase in awareness of cases of sexual abuse within Christian circles. This essay will argue for the relevance as Hagar, long an important symbolic figure for the oppressed, as a biblical symbolic parallel for victims/survivors of abuse within the church. In viewing sexual abuse through this lens, I will also be considering relevant insights and applications for the church.